Preliminary Study of S-Wave Velocity and Unconfined Compressive Strength of Cement- Palf Stabilised Kaolin - Chan, Chee Ming; Ch'ng, S.S. (International Journal of Integrated Engineering, 2011)
Clays are notoriously well known for giving rise to myriad problems and difficulties inconstruction due to excessive settlement and limited strength. Hence, there is a need to pretreatthe soils prior to construction, such as improving the engineering properties via thestabilisation technique, before additional load can be applied on it. In soil stabilisation,cement is commonly used as a stabilizing agent, to simultaneously increase the strength andstiffness of the originally weak, soft material. However cement is relatively expensive andpotentially harmful to the environment when admixed with soils. The need for alternativestabilizing agents which could reduce the use of cement is therefore apparent. In this study,natural fibres were retrieved from pineapple leaves, an agricultural waste product typical ofJohor. Next pre-determined quantities of pineapple leaf fibres (PALF) were added to anartificial clay, kaolin, together with cement. The mixture was formed into specimens of 38mm diameter and 76 mm high, cured in dry condition before being subjected to the s-wavevelocity and unconfined strength measurements. A range of curing period was introduced toexamine the effect of time on the performance of the stabilised specimens too. It was foundthat the fibres function as a form of reinforcement to the soil. Also, the test data revealed thatPALF alone makes negligible contribution to the improved properties, where cement isnecessary to act as a binder to strengthen the soil matrix. Nevertheless the potential of usingPALF as an additive to cement in soft soil stabilisation is promising, though further work isnecessary to better understand the stabilised material and its long term performance.